Effects of the COVID-19 pandemic on general health and malaria control in Ghana: a qualitative study with mothers and health care professionals - Anna-Katharina Heuschen; Alhassan Abdul-Mumin; Abdulai Abubakari; Faith Agbozo; Guangyu Lu; Albrecht Jahn; Olaf Müller (Malaria Journal, 2023)
Abstract Background COVID-19 has severely impacted health systems and the management of non-COVID-19 diseases, including malaria, globally. The pandemic has hit sub-Saharan Africa less than expected; even considering large underreporting, the direct COVID-19 burden was minor compared to the Global North. However, the indirect effects of the pandemic, e.g. on socio-economic inequality and health care systems, may have been more disruptive. Following a quantitative analysis from northern Ghana, which showed significant reductions in overall outpatient department visits and malaria cases during the first year of COVID-19, this qualitative study aims to provide further explanations to those quantitative findings. Methods In the Northern Region of Ghana, 72 participants, consisting of 18 health care professionals (HCPs) and 54 mothers of children under the age of five, were recruited in urban and rural districts. Data were collected using focus group discussions with mothers and through key informant interviews with HCPs. Results Three main themes occurred. The first theme—general effects of the pandemic—includes impacts on finances, food security, health service provision as well as education and hygiene. Many women lost their jobs, which increased their dependance on males, children had to drop out of school, and families had to cope with food shortages and were considering migration. HCPs had problems reaching the communities, suffered stigmatisation and were often barely protected against the virus. The second theme—effects on health-seeking—includes fear of infection, lack of COVID-19 testing capacities, and reduced access to clinics and treatment. The third theme—effects on malaria—includes disruptions of malaria preventive measures. Clinical discrimination between malaria and COVID-19 symptoms was difficult and HCPs observed increases in severe malaria cases in health facilities due to late reporting. Conclusion The COVID-19 pandemic has had large collateral impacts on mothers, children and HCPs. In addition to overall negative effects on families and communities, access to and quality of health services was severely impaired, including serious implications on malaria. This crisis has highlighted weaknesses of health care systems globally, including the malaria situation; a holistic analysis of the direct and indirect effects of this pandemic and an adapted strengthening of health care systems is essential to be prepared for the future.